Taguchi approach on surface integrity of titanium in turning operation using tin coated cutting tool - Aida Azwa, A. Halim (2010)
Modern manufacturers, seeking to remain competitive in the market, rely on their manufacturing engineers and production personnel to quickly and effectively set up manufacturing process for new products. Taguchi Parameter design is a powerful and efficient method for optimizing quality and performance output of manufacturing processes, thus a powerful tool for meeting this challenge. This thesis discusses an investigation into use the Taguchi Parameter Design for optimizing surface roughness generated by a Computer Numerical Controller (CNC) lathe. Control parameters being consider in this thesis are cutting speed, feed rate and depth of cut. After experimentally turning sample workpiece using the selected orthogonal array and the parameters, this study expected produce an optimum combination of controlled parameter for the surface roughness. And from the result generated, the correlation for surface roughness with the cutting parameters satisfies a reasonable degree of approximation. Cutting speeds are a significant parameter in influencing the surface roughness.